Celiac Disease: Extraintestinal Manifestations and Associated Conditions. Issue 1 (January 2020) - Therrien, Amelie; Kelly, Ciaran P.; Silvester, Jocelyn A.
Abstract : Celiac disease is a common form of enteropathy with frequent extraintestinal manifestations (EIM). Misrecognition of these presentations may lead to significant delays in diagnosis. Any organ may be involved, either through an immune/inflammatory phenomenon, or nutritional deficiencies. Some EIM, such as gluten ataxia, may be irreversible if left untreated, but most will improve with a gluten-free diet. Knowledge of the various EIM, as well as the associated conditions which do not improve on a gluten-free diet, will avoid delays in the diagnosis and management of celiac disease and associated manifestations.